Spectral-domain optical coherence tomography imaging of macula-off rhegmatogenous retinal detachment - Sridhar J (Dove Medical Press, 2014)
Jayanth Sridhar, Harry W Flynn Jr Department of Ophthalmology, Bascom Palmer Eye Institute, Miami, FL, USA Abstract: The timing of repair and the utility of spectral-domain optical coherence tomography (SD-OCT) for macula-off retinal detachment remains a controversial issue. Four patients who presented with macula-off retinal detachment underwent repair at various time points after symptom onset. Postoperative SD-OCT of the macula demonstrated correlation with final visual acuity. Keywords: SD-OCT, vitrectomy, scleral buckle